A normal electrocardiogram indicates a better prognosis in patients with moderate to very severe chronic obstructive pulmonary disease - Martina Kulirova; Miroslav Solar; Michal Kopecky; Barbora Novotna; Marek Plutinsky; Kristian Brat; Libor Fila; Petr Vanik; Pavlina Musilova; Tomas Dvorak; Petr Safranek; Michal Svoboda; et al. (Scientific Reports)
Abstract The role of electrocardiography (ECG) in predicting mortality in patients with chronic obstructive pulmonary disease (COPD) has not been sufficiently established. Research question: Is a normal ECG associated with a better prognosis than an abnormal ECG in patients with COPD? ECG parameters were assessed in patients enrolled in the Czech Multicenter Research Database of COPD. We assessed ECGs from baseline (August 2013) until December 31, 2019, or until death. The primary endpoint was 5-year overall survival depending on the ECG findings. A total of 300 subjects were enrolled in the study and 143 died during follow-up. This multicenter noninterventional observational prospective study revealed a significant difference in 5-year overall survival between COPD patients with normal ECGs and those with prognostically significant or other ECG abnormalities (76.8%, 38.2%, and 63.4%, respectively; P < 0.001). Patients with prognostically significant ECG abnormalities had a 2.537-fold greater mortality risk at 5 years than those with normal ECGs. In the COPD setting, patients with normal ECGs had a better prognosis than those with prognostically significant abnormalities suggesting that ECG may be a valuable tool for predicting mortality risk in these patients.